THE TYPE, AMOUNT, AND DEGREE OF INFESTATION OF WEEDS FOUND IN PEAS - Turdieva Nilufar Muminovna; Umarov Akbar; Yuldоshоv Abdulaziz; Rasulova Zuxro Alisherovna; Kalandarova Maftuna; Togaeva Dilnura; Togaev Shohrukh (Galaxy International Interdisciplinary Research Journal, 2022)
Types and quantities of weeds in mosh fields, rate of occurrence The Weeds reduce the productivity of the agricultural cultures, worsen the quality to product. Under average sowing productivity falls on 20-25%, but under strong in general possible not to get the harvests.